Analisis Kesulitan Membaca dan Menulis pada Siswa Kelas II Sekolah Dasar - Angel Anastasia Kristianty Saragih; Sih Widayati; Agung Setyawan (Citra Dharma Cindekia, 2024)
This study aims to find problems in UPTD SDN Tanjung Jati II. One of the problems found is that not all students master reading and writing activities so it is important to conduct research to review the problem. This method uses qualitative research. Data collection used in this study is observation, tests, interviews and documentation. The data analysis technique used is the Milles and Huberman model with stages, data reduction, data presentation, and conclusions. UPTD SDN Tanjung Jati 2 consists of 12 students in class II. Of the 12 students, there are 4 students who are limited when reading and writing. Students who can read and write accurately will find it easy to follow the learning, while students who are lacking will find it difficult to follow the learning. This often results in them being left behind when following the learning.